A New Model of Stakeholder Participation in Village Development Planning - Dayadi, Dayadi; Ahmad, Jamaluddin; Jabbar, Abdul; Astuti, Yayuk (Jurnal Studi Ilmu Pemerintahan, 2024)
This research aims to develop and evaluate a stakeholder engagement model in development planning in Bina Baru village, Sidenreng Rappang Regency through the ‘Ladda-Ladda’ approach. The model aims to improve community participation and coordination between the government and the community in the village development planning process. Qualitative research methods were used, with participant observation and in-depth interviews as the main data collection techniques. Data analysis was conducted through thematic coding to identify patterns and emerging themes related to stakeholder engagement. The research findings show that the implementation of the ‘Ladda-Ladda’ model has succeeded in increasing the active participation of the community, which is reflected in their increased involvement in expressing their aspirations and participating in village deliberations. This strengthens social relations and trust between the community and the government, resulting in a more relevant and inclusive development plan. Theoretically, this study contributes to the literature on village development by integrating the concepts of community participation and coordination theory into a model that can be applied in different villages. However, this study has limitations in generalizing the results because the study was conducted in only one village. In addition, the implementation of this model requires significant time and resources, especially in building community participation capacity. Further research is needed to test the effectiveness of this model in a broader context and to develop more efficient strategies for its implementation.